(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
This study was aimed to economic evaluation of using of sugar beet for fattening Jinding duck. A total number of 160, male one day old, Jinding ducklings were used in this study. All ducks were weighed individually and distributed randomly among 4 treatments, each treatment includes 40 ducklings were nearly similar in initial average body weights and each treatment was 4 blocks of 13 ducklings. Chemical analysis for rations was applied and different productive and economic measures applied. The results showed significant differences (p>0.05) among all groups for the final body weight where the control groups it was 389.40±251.87 gram and for T2, T3, and T4 the final body weight were 641.93±503.98, 693.55±500.33, 693.55±500.33 respectively. And also there were significant differences (p< 0.05) among all groups for the total feed intake were at the control groups it was 903.83±467.34 and for the T2, T3, and T4 for the total feed intake were 792.70±483.25, 845.60±471.20 and 833.98±465.28 gram respectively. The feed conversion rate showed significant difference (p<0.05) among all groups where at the control groups it was 3.049, and for T2, T3 and T4 the feed conversion rate were 1.836, 1.615, 1.779 respectively. The highest gross margin and Benefit Cost Ration (Tk.153.19/per duck and 1.47 respectively) were obtained from T2 and the lowest (Tk. 122.78/duck and 1.35 respectively) from T4. Finally, we concluded that the using of sugar beet as a percentage with the concentrate feed has no side effect on the final growth weight of the Jinding ducks and through this research work the 10% is more economic than 20 % and 15% so we concluded that using sugar beet with 10% of the total concentrate feed to the ration of the Jinding ducks but FCR was found in 15% sugar beet mixed feed better. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (3), 238-242